Os conteúdos de ensino da Educação Física: produções acadêmicas e representações de alunos finalistas do Ensino Fundamental - Ribeiro, Bruna Almeida (2021)
This research has as object of study teaching contents of Physical Education (PE). The objectives are: a) producing a systematic review of PE teaching contents in Elementary School, from 2009 to 2019, in order to establish a State of Knowledge on the subject, identifying advances and gaps in academic-scientific production; b) Analyze, through the speeches of finalist students of Elementary School, their representations about the teaching contents experienced in this phase of Basic Education; c) Discuss, based on the mapped production and the produced discourses, the pedagogical treatment of the teaching contents in the Physical Education classes. To do so, it combines two methodologies: the Exploratory Systematic Review with the Descriptive-Interpretive Research. For data production, the first methodology uses four international databases as source: Latin American Literature for Health Sciences (LILACS), Scientific Electronic Library Online (SciELO), SCOPUS and Portal de Periódicos da Capes. In the second methodology, the data came from interviews with 9th grade students and were interpreted through Content Analysis, in dialogue with Michel de Certeau's Studies with Everyday Life, and Bernard Charlot's theory of the Relationship with Knowledge. The results have showed that sport remains the hegemonic content, both in academic productions and in PE classes. However, upon entering the specificity of the articles and the interviews, we found out that different approaches affect this manifestation of the culture of movement, explaining its polysemic character. Different contents also emerge in this investigation, revealing alternatives for the mediation of PE in the school context. The Systematic Review highlights the authors who most published on the topic of teaching content and the methods/instruments used. Of the 141 articles found, 46 articles had students as research subjects, who were grouped into three categories of analysis: student representations, gender and specific content. Despite listening to students, a few researches has sought to understand the meanings and expectations of these subjects in relation to PE teaching content. Most of the texts focus on the students' opinion on the pedagogical strategies adopted by the teachers, thus explaining the peripheral place that the students occupy in these researches. The interviews, which focus on students' representations about PE and its teaching content, highlight the following themes: separation of classes by gender; posture (neglect/commitment) of the teacher with his pedagogical practices; health as a justification for PE at school; sports rules and fundamentals as appropriate learning in PE classes; leisure as a dimension of life in which PE appropriations are manifested; and the attitudinal dimension of the content.